Drama as a Tool of Social Conflict Management: “Jalan Asmaradana” Performance Project - Nurhasanah, Een; Hussin, Hanafi (Humanus, 2022)
This study examines the process of the drama staging project "Jalan Asmarandana" adapted from the short story by Kuntowijoyo. The research problem concerns, how can drama become a tool for social conflict management? as for the object of analysis in the form of process data for the drama staging project "Jalan Asmarandana" by students in the fifth semester of the 2018 academic year, the Indonesian Language and Literature Education study program, Faculty of Teacher Training and Education, University of Singaperbangsa Karawang. The theory used in analyzing the data is Dorothy Heathcote's theory, as a theory of conflict resolution approach, namely as-if experience, reflection, and negotiation. The method used is descriptive qualitative method. The results of the research students might feel like they are someone else with the as-if experience training project, and it has been offered multiple views on an issue encountered by students through the roles they play. Reflection teaches us that life is a sequence of experiences tinted by life's issues at all times. Drama is a reflection of life. Finally, negotiation training gives students indirect experience with how to communicate, collaborate, and discuss with a group, particularly the drama production team.